Method for preparing asphalt-based porous carbon based on MgO template
By using commercial nano MgO templates and petroleum asphalt, combined with potassium hydroxide, porous carbon materials are prepared, which solves the problems of unstable preparation process and high cost in the existing technology, and realizes the preparation of high-performance porous carbon materials, which is suitable for supercapacitors. application.
Patent Information
- Application Number
- CN202411493179.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the preparation process of carbon-based electrode materials is unstable, costly, and difficult to achieve large-scale production, which affects the realization of high energy density and high power density of supercapacitors.
Nanoporous sheet MgO is prepared by hydrothermal synthesis using commercial nano-MgO templates, combining petroleum asphalt and potassium hydroxide, and by adjusting the proportion of template agent and activator, porous carbon materials are prepared by hydrothermal method and calcination method, replacing coal asphalt and Complex natural rock asphalt improves the performance and preparation efficiency of materials.
The preparation of high-performance porous carbon materials is realized, which reduces costs, increases the specific surface area and pore volume of the material, enhances the electrochemical performance, and is suitable for large-scale production and supercapacitor applications.
Smart Images

Figure CN119240695A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of porous carbon, and in particular to a method for preparing asphalt-based porous carbon based on a MgO template. Background Art
[0002] Porous carbon has attracted extensive attention due to its high specific surface area, excellent conductivity, low cost and environmental friendliness. In order to achieve supercapacitors with high energy density and high power density, the research strategy of carbon electrode materials focuses on creating a large number of micropores for charge accumulation to improve the specific capacitance and an appropriate amount of mesopores to optimize the rapid transfer of ions. Although the research on carbon-based electrode materials has achieved some gratifying results, from the perspective of practical application, it is still urgent to explore a controllable, economical and easy-to-implement technology for preparing high-performance porous carbon materials.
[0003] Patent CN106430144A discloses a method for preparing asphalt-based hierarchical porous carbon sheets based on a flaky magnesium oxide template and its application. The material used is coal tar pitch, and the source and composition of coal tar pitch are relatively complex, which may lead to increased instability and uncontrollability during the preparation process. Its pore structure is usually more complex, while the processing process of natural rock asphalt is complex, the source of materials is limited, and the cost is also high, which is not conducive to the large-scale production of porous carbon. Summary of the invention
[0004] The purpose of the present application is to provide a method for preparing asphalt-based porous carbon based on MgO template, wherein commercial nano-MgO is used to prepare nanoporous flaky MgO through a hydrothermal synthesis method, petroleum asphalt is used instead of coal asphalt, and the performance of the obtained porous carbon material is improved by adjusting the amount of flaky porous MgO incorporated and the amount of KOH activator added.
[0005] The present invention provides a method for preparing asphalt-based porous carbon based on MgO template. The method for preparing asphalt-based porous carbon based on MgO template comprises the following preparation steps: Step 1: Mix nano-MgO with deionized water, place in a synthesis reactor, perform hydrothermal synthesis at 180°C for 2h, filter, dry in an oven at 100°C, grind the dried filter cake in a mortar, and finally calcine in a muffle furnace at 550°C for 1h to obtain porous flake MgO; Step 2: preparing asphalt solution and MgO suspension; Step 3: Add the asphalt solution obtained in step 2 dropwise into the MgO suspension, mix and stir, and dry at 60° C. to remove the solvent tetrahydrofuran to obtain a brown powder; Step 4: transferring the brown powder obtained in step 3 into a corundum crucible and placing it in a tube furnace, and calcining it under an argon protective atmosphere to obtain a carbonized C / MgO composite material; Step 5: washing the carbonized C / MgO composite material obtained in step 4 with a dilute hydrochloric acid solution and deionized water to obtain a carbon material sample, which is recorded as AC-75; Step 6: Pour AC-75 and KOH into a mortar and grind them thoroughly, then transfer the mixture to a tube furnace and calcine under an argon protective atmosphere to obtain an activated product; Step 7: The activated product obtained in step 6 is acid-washed and water-washed until neutral, and then placed in a vacuum drying oven and dried at 60° C. for 12 hours to obtain a porous carbon material PCs.
[0006] Preferably, in step 1, the mass ratio of nano-MgO to deionized water is 1:10.
[0007] Preferably, in step 2, the amount of porous flake MgO added is 75% of the mass of petroleum asphalt.
[0008] Preferably, in step 4, the calcination conditions are 5°C min -1 The heating rate was increased to 500°C and maintained for 2 h.
[0009] Preferably, in step six, the mass ratio of AC-75:KOH is 1:1.
[0010] Preferably, the calcination condition in step six is 5°C min -1 The heating rate was increased to 800°C and heated for activation for 2 hours.
[0011] Preferably, the specific steps of preparing the asphalt solution and the MgO suspension in step 2 are: taking petroleum asphalt and the porous flake MgO obtained in step 1, adding them to tetrahydrofuran respectively and stirring evenly to obtain the asphalt solution and the MgO suspension.
[0012] Therefore, the present application provides a method for preparing asphalt-based porous carbon based on MgO template, which has the following beneficial effects: 1) Petroleum asphalt has a high carbon content, is widely available and is inexpensive.
[0013] 2) The selected magnesium oxide template has high chemical stability and thermal stability. It does not react with the carbon source during the carbonization reaction and can be removed by dilute acid after the reaction. Therefore, it is very suitable as a template for preparing porous carbon materials. The preparation method of flaky magnesium oxide is simple and easy to realize industrial production.
[0014] 3) In the present invention, the mass ratio of flaky magnesium oxide and potassium hydroxide is controlled to be 1:1 to improve its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 GCD diagrams of porous carbon materials PCs obtained in Example 1 and Comparative Examples 1-4; Figure 2 The porous carbon material PCs obtained in Example 1 1 SEM images of Figure 3 The porous carbon material PCs obtained in Example 1 1 TEM images of Figure 4 The porous carbon material PCs obtained in Example 1 1 XRD patterns of porous carbon materials PCs obtained with AC-75 and Comparative Examples 1-4; Figure 5 The porous carbon material PCs obtained in Example 1 1 , AC-75 and AC-0 pore size distribution diagram; wherein AC-0 is the material obtained in Example 1 without adding the template agent and the KOH activator; Figure 6 The porous carbon material PCs obtained in Example 1 1 of Laguna; Figure 7 The porous carbon material PCs obtained in Example 1 1 Raman spectra of the porous carbon materials PCs obtained with AC-75 and Comparative Examples 1-4; Figure 8 The porous carbon material PCs obtained in Example 1 1 , AC-75 and AC-0 nitrogen adsorption-desorption isotherms, wherein AC-0 is the material obtained in Example 1 without adding the template agent and the KOH activator; Fig. 9 is the mass specific capacitance of PCs at different current densities calculated by GCD curve. DETAILED DESCRIPTION
[0016] The technical solution of the present invention is further illustrated by the following examples.
[0017] Example 1 The method for preparing pitch-based porous carbon based on MgO template is as follows: Step 1 Preparation of porous flaky magnesium oxide template The flaky porous MgO template was prepared by hydrothermal synthesis. 5 g of commercial nano-MgO (30-50 nm) was mixed with deionized water in a mass ratio of 1:10, placed in a synthesis reactor, and hydrothermally synthesized at 180°C for 2 h. The mixture was filtered and dried in an oven at 100°C. The dried filter cake was crushed in a mortar and finally calcined in a muffle furnace at 550°C for 1 h to obtain porous flaky MgO.
[0018] Step 2 Preparation of porous carbon Asphalt-based porous carbon materials were prepared using porous flake MgO as a template, KOH as an activator, 70# road petroleum asphalt as a carbon source, tetrahydrofuran as a solvent, and hydrochloric acid as a cleaning agent. The specific preparation steps are as follows: (1) Take 1.5 g petroleum asphalt and 1.125 g porous flake MgO (75% of the mass of the asphalt) and add them to 30 mL and 20 mL tetrahydrofuran respectively and stir evenly; (2) adding the asphalt solution dropwise into the MgO suspension, mixing and stirring for 5 h, and drying at 60 °C to remove the solvent tetrahydrofuran to obtain a dark brown powder; (3) The powder was transferred to a corundum crucible and placed in a tube furnace. Under an argon protective atmosphere, the temperature was 5 °C min -1 The heating rate was raised to 500°C and maintained for 2h; (4) The C / MgO composite material obtained after carbonization was treated with 1 molL -1 The carbon material sample obtained after washing with dilute hydrochloric acid and deionized water was recorded as AC-75.
[0019] (5) Pour AC-75 and KOH in a mortar at a mass ratio of 1:1 and grind thoroughly. Then transfer the mixture to a tube furnace and heat at 5°C min-1 in an argon atmosphere. -1 The heating rate was increased to 800°C and heated for activation for 2 hours.
[0020] (6) The activated product was then acid-washed and washed with water until neutral, and then placed in a vacuum drying oven and dried at 60°C for 12 h to obtain a porous carbon material PCs. 1 .
[0021] Comparative Example 1 Porous carbon material PCs of Comparative Example 1 0.1 In the preparation method, the mass ratio of AC-75:KOH is 1:0.1, and the remaining steps are the same as those in Example 1.
[0022] Comparative Example 2 Porous carbon material PCs of Comparative Example 2 0.5 In the preparation method, the mass ratio of AC-75:KOH is 1:0.5, and the remaining steps are the same as those in Example 1.
[0023] Comparative Example 3 Porous carbon material PCs of Comparative Example 3 1.5 In the preparation method, the mass ratio of AC-75:KOH is 1:1.5, and the remaining steps are the same as in Example 1.
[0024] Comparative Example 4 Porous carbon material PCs of Comparative Example 4 2 In the preparation method, the mass ratio of AC-75:KOH is 1:2, and the remaining steps are the same as those in Example 1.
[0025] Comparative Example 5 The asphalt used in Comparative Example 5 is natural rock asphalt, and the remaining steps and parameters are the same as those in Example 1. The porous carbon for superelectric is prepared using Butun rock asphalt as raw material, and the specific surface area of the material is 795.96 m 2 / g, the specific capacitance of the electrode at currents of 2.0A / g and 10.0A / g are 211F / g and 165F / g, respectively.
[0026] Comparative Example 6 The asphalt used in Comparative Example 6 is coal tar pitch, and the remaining steps and parameters are the same as those in Example 1. The porous carbon for superelectric is prepared using coal tar pitch as raw material. The specific capacity of the coal tar pitch-based porous carbon electrode is 1Ag -1 290Fg -1 。
[0027] Figure 2 The SEM images show that PCs 1 The surface has rich, interconnected pore structures, and the mesopores and macropores are clearly visible. The mesopores and macropores can promote ion diffusion and facilitate the penetration of electrolytes. It can also be seen from the figure that PCs 1 It has a flaky structure and thin layers. The thin layer structure can shorten the transmission distance of ions, increase the conductivity of the electrode material, and improve the rate performance of the supercapacitor.
[0028] Figure 3 Medium PCs 1 The TEM image shows that it has a distinct hierarchical pore structure. The macropores are clearly visible with a pore size of 50-100 nm. These macropores are inherited from the MgO template and enlarged by KOH activation. The pores are evenly distributed, with micropores being the main part, and mesopores and macropores scattered around the micropores. PCs 1 The sheets are interconnected and contain a large number of micropores. The presence of micropores provides a large surface area to enhance the charge storage capacity and improve the specific capacity of the electrode material.
[0029] Figure 4 Figure 2 is the XRD diagram of AC-75 and PCs porous carbon materials. The samples show two broad peaks near 23° and 43°, representing the (002) and (100) crystal plane diffraction peaks of graphite, respectively. The weaker and wider the peak intensity corresponding to the (002) crystal plane diffraction peak, the higher the degree of disorder. It can be seen from the figure that the 002 peak of PCs is significantly weaker than that of AC-75 and becomes gentle, indicating that the activation effect of KOH will destroy the graphitized structure of the carbon material. 1 、PCs 1.5 、PCs 2 The peak at 23° is weak and broad, indicating a high degree of disorder.
[0030] Figure 8 The isotherms of nitrogen adsorption-desorption of various carbon materials are shown in Figure 2. The curve of AC-0 material without MgO template and KOH activator is almost flat, and the adsorption and desorption amount is extremely low, indicating that there is almost no pore structure. 0 <0.01, AC-75 and PCs 1 The isotherm adsorption line has a steep increase trend, which is a typical microporous structure; at the relative pressure p / p 0 =0.4~0.95, there is an obvious hysteresis loop, indicating that there are abundant mesopores inside; relative pressure p / p 0 When it is close to 1.0, the adsorption amount increases sharply, and the adsorption isotherm shows a slight "tailing", which confirms the presence of macropores in the material. Compared with AC-0, the nitrogen adsorption amount of AC-75 increases, indicating that the MgO template has a pore-forming effect. 1 The nitrogen adsorption capacity of the material is far greater than that of AC-75, indicating that its specific surface area and pore volume have increased significantly. KOH can significantly increase the pore volume of the material. The pore size distribution curve of the carbon material is shown in Figure 2. Figure 5 As shown in the figure. The AC-0 material is a straight line parallel to the x-axis, indicating that it has almost no pore structure; AC-75 presents a bimodal distribution, which is a shoulder peak of micropores below 2nm and a small mesopore peak centered at 4nm. These small amounts of micropores and mesopores come from the occupancy of the MgO template and the stacking gap of the carbon sheet; PCs 1 There are three pore size distribution peaks, the micropore shoulder peak below 2nm increases significantly, the small mesopore peak centered at 4nm remains almost unchanged, and a medium mesopore broad peak centered at 10nm appears. These abundant micropores and a certain amount of mesopores are mainly derived from KOH activation. This multi-level pore structure is an ideal choice for high-performance supercapacitor electrode materials.
[0031] Figure 7 The Raman spectra of various carbon materials are shown in the figure. It can be seen that the samples have a Raman spectrum at 1335 cm -1 (D band) and 1585cm -1 Two significant characteristic peaks of carbon materials appear at (G band), corresponding to disordered / defective carbon and graphite carbon respectively. The intensity ratio of D peak to G peak (I D / I G ) can be used to characterize the degree of graphitization of carbon materials, and also reflects the degree of defects in carbon materials. The intensity ratio of D peak to G peak (I D / I G ) is larger, indicating that the degree of graphitization of PCs is lower and the defects are more. AC-75, PCs 0.1 、PCs 0.5 、PCs 1、PCs 1.5 、PCs 2 I D / I G The values are 0.46, 1.02, 1.11, 1.16, 1.25, and 1.27, respectively. It can be seen that with the increase of KOH addition, I D / I G The value gradually increases, indicating that KOH will increase the disorder and defect structure and reduce the graphitization degree of PCs, which is consistent with the results of XRD reaction.
[0032] Figure 1 For PCs materials at 1Ag -1 The GCD curves under the above conditions are all highly symmetrical isosceles triangles, indicating that PCs have typical double-layer capacitor characteristics and good electrochemical reversibility. In order to further reveal the rate performance of PCs, the mass specific capacitance at different current densities calculated by the GCD curves are shown in Figure 2. Fig. 9 As shown in the figure, the specific capacitance of all samples decreases with the increase of current density. This is because increasing the current density will reduce the charging time, and some micropores fail to effectively adsorb electrolyte ions, and the amount of stored charge decreases. -1 The specific capacitances are 247, 344, 376, 244, and 200 Fg respectively. -1 , at 10Ag -1 The specific capacitance at current density is 190, 240, 300, 200, 140 Fg respectively -1 The capacity retention rates were 76.9%, 69.7%, 79.8%, 81.9% and 70.0% respectively for PCs 1 It not only exhibits the highest mass specific capacitance, but also has excellent rate performance.
[0033] data: After the carbon material with MgO template added in an amount of 75% was activated by KOH in a mass ratio of 1:1, the specific surface area and pore volume of the prepared PCs1 were 1388 m 2 g -1 、1.9cm 3 g -1 , presenting a lamellar multi-level pore structure and having excellent supercapacitor performance.
[0034] In the three-electrode system, PCs 1 It has typical double-layer capacitor characteristics and good electrochemical reversibility. -1 The specific capacitance at current density is 376 and 300 Fg respectively -1 For the two-electrode system, PCs 1 Symmetrical supercapacitor at 0.5Ag-1 The specific capacitance is 85Fg -1 , at 499.2Wkg -1 The energy density at the power density is 10.4Whkg -1 After 10,000 constant current charge and discharge cycles, at 1Ag -1 The capacity retention rate is 80%, showing excellent electrochemical performance.
[0035] Therefore, the present application provides a method for preparing asphalt-based porous carbon based on MgO template, and the obtained petroleum asphalt-based porous carbon material has stable performance and low material price.
[0036] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0037] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing pitch-based porous carbon based on MgO template, characterized in that: The method for preparing pitch-based porous carbon based on MgO template includes the following preparation steps: Step 1: Mix nano-MgO with deionized water, place in a synthesis reactor, perform hydrothermal synthesis at 180°C for 2h, filter, dry in an oven at 100°C, grind the dried filter cake in a mortar, and finally calcine in a muffle furnace at 550°C for 1h to obtain porous flake MgO; Step 2: preparing asphalt solution and MgO suspension; Step 3: Add the asphalt solution obtained in step 2 dropwise into the MgO suspension, mix and stir, and dry at 60° C. to remove the solvent tetrahydrofuran to obtain a brown powder; Step 4: transferring the brown powder obtained in step 3 into a corundum crucible and placing it in a tube furnace, and calcining it under an argon protective atmosphere to obtain a carbonized C / MgO composite material; Step 5: washing the carbonized C / MgO composite material obtained in step 4 with a dilute hydrochloric acid solution and deionized water to obtain a carbon material sample, which is recorded as AC-75; Step 6: Pour AC-75 and KOH into a mortar and grind them thoroughly, then transfer the mixture to a tube furnace and calcine under an argon protective atmosphere to obtain an activated product; Step 7: The activated product obtained in step 6 is acid-washed and water-washed until neutral, and then placed in a vacuum drying oven and dried at 60° C. for 12 hours to obtain a porous carbon material PCs.
2. The method for preparing pitch-based porous carbon based on MgO template according to claim 1, characterized in that: In step 1, the mass ratio of nano-MgO to deionized water is 1:
10.
3. The method for preparing pitch-based porous carbon based on MgO template according to claim 2, characterized in that: In step 2, the amount of porous flake MgO added is 75% of the mass of petroleum asphalt.
4. The method for preparing pitch-based porous carbon based on MgO template according to claim 1, characterized in that: In step 4, the calcination conditions are 5°C min -1 The heating rate was increased to 500°C and maintained for 2 h.
5. The method for preparing pitch-based porous carbon based on MgO template according to claim 1, characterized in that: In step six, the mass ratio of AC-75:KOH is 1:
1.
6. The method for preparing pitch-based porous carbon based on MgO template according to claim 1, characterized in that: The calcination conditions in step 6 are 5°C min -1 The heating rate was increased to 800°C and heated for activation for 2 hours.
7. The method for preparing pitch-based porous carbon based on MgO template according to claim 1, characterized in that: The specific steps of preparing the asphalt solution and the MgO suspension in step 2 are: taking petroleum asphalt and the porous flake MgO obtained in step 1, adding them to tetrahydrofuran respectively and stirring them evenly to obtain the asphalt solution and the MgO suspension.
Citation Information
Patent Citations
Method for preparing asphalt-based hierarchical porous carbon sheet based on sheet-shaped magnesium oxide template and application thereof
CN106430144A
Nitrogen-doped porous graphene-class carbon nanosheet material, and preparation method and application thereof
CN109494082A
Preparation method of porous carbon, porous carbon prepared by preparation method and application of porous carbon
CN112830472A
Porous carbon sheet
WO2015137107A1
Cited By
Rock asphalt-based porous carbon spherical particles and preparation method thereof
CN120117606A
Preparation method of waste asphalt carbon with microcrystalline vortex structure as ion battery material
CN120229705A
Asphalt-based hard carbon material with multi-source asphalt precursor-based multi-dimensional closed-pore structure, preparation method and application
CN122380350A
A multi-source asphalt precursor-based multi-dimensional closed-pore structure asphalt-based hard carbon material, a preparation method and applications thereof
CN122380350B
Porous structure controllable carbon material, preparation method thereof and electrochemical energy storage device
CN122725242A
